Greetings from the Graveyard - Klise, Kate. (Boston ; New York : Houghton Mifflin Harcourt, 2014)
"The unsuspecting trio at Spence Mansion starts a greeting card company--and winds up on the adventure of a lifetime!"--
Keywords: Letters -- Fiction; Greeting cards -- Fiction; Authors -- Fiction; Ghosts -- Fiction; Dwellings -- Fiction; Haunted houses -- Fiction; Humorous stories; Letters -- Juvenile fiction; Greeting cards -- Juvenile fiction; Authors -- Juvenile fiction; Dwellings -- Juvenile fiction; Haunted houses -- Juvenile fiction; Humorous stories